2020
DOI: 10.1002/ajh.25766
|View full text |Cite|
|
Sign up to set email alerts
|

Frontline treatment with the combination obinutuzumab ± chlorambucil for chronic lymphocytic leukemia outside clinical trials: Results of a multinational, multicenter study by ERIC and the Israeli CLL study group

Abstract: In recent years, considerable progress has been made in frontline therapy for elderly/physically unfit patients with CLL. The combination of obinutuzumab and chlorambucil (O-Clb) has been shown to prolong progression free survival (PFS, median PFS-31.5 months) and overall survival (OS) compared to chlorambucil alone. More recently, obinutuzumab given in combination with either ibrutinib or venetoclax improved PFS but not OS when compared to O-Clb. In this retrospective multinational, multicenter co-operative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…18 Likewise, an 80.3% ORR and estimated 2-year OS of 88% was recorded by the Israeli end ERIC group in elderly patients who received chlorambucil and obinutuzumab, without unexpected adverse events. 32 Taken together, these data show that the efficacy and safety of different CIT regimens in routine clinical practice are consistent with those reported in clinical trials.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…18 Likewise, an 80.3% ORR and estimated 2-year OS of 88% was recorded by the Israeli end ERIC group in elderly patients who received chlorambucil and obinutuzumab, without unexpected adverse events. 32 Taken together, these data show that the efficacy and safety of different CIT regimens in routine clinical practice are consistent with those reported in clinical trials.…”
Section: Discussionsupporting
confidence: 84%
“…It is worth noting that chlorambucil and rituximab produced an 87% ORR with an OS rate at 48 and 60 months of 86.1% (95% CI: 79.4‐93.5) and 81.2% (95% CI: 72.4‐91.2), respectively, in elderly patients treated outside clinical trials 18 . Likewise, an 80.3% ORR and estimated 2‐year OS of 88% was recorded by the Israeli end ERIC group in elderly patients who received chlorambucil and obinutuzumab, without unexpected adverse events 32 . Taken together, these data show that the efficacy and safety of different CIT regimens in routine clinical practice are consistent with those reported in clinical trials.…”
Section: Discussionmentioning
confidence: 90%
“…This treatment showed a complete remission rate of 32%, but also the occurrence of toxicities as tumor lysis syndrome [ 30 ]. The efficacy of G-Chl regimen in CLL patients with comorbidities has been assessed in CLL11 trial [ 5 , 31 ], which led to its approval by FDA and EMA as a first-line treatment in patients with comorbidities (CIRS > 6 and/or CrCl < 70 mL/min) and in real-life studies [ 32 , 33 ]. The CLL11 study also showed that Chl-R achieves longer PFS (median 16 versus 11 months) and overall survival (OS) than chlorambucil monotherapy.…”
Section: Therapeutic Approaches In Older And/or Unfit Patient Populationsmentioning
confidence: 99%
“…Real-world data from our group and others show that patients receiving Clb-based regimens have a median age of 76–80 years, and it remains to accurately determine these patients’ tolerance of targeted treatment and need for supportive care. 22 , 49 …”
Section: Discussionmentioning
confidence: 99%